The Beginnings of Pancreatology as a Field of Experimental and Clinical Medicine - Ceranowicz, Piotr (Biomed Res Int, 2015)
This review presents the history of discoveries concerning the pancreas. In antiquity and the Middle Ages knowledge about the anatomy of the pancreas was very limited and its function was completely unknown. Significant progress was first made in the seventeenth and eighteenth centuries. Johann Georg Wirsüng, the prosector of the University of Padua, discovered the main pancreatic duct, and Giovanni Santorini discovered the accessory duct. Regnier de Graaf was the first to perform pancreatic exocrine studies, and Paul Langerhans's 1869 discovery of pancreatic islets was the first step toward recognizing the pancreas as an endocrine gland. The twentieth century brought the discovery of insulin and other pancreatic hormones. To date, histochemical staining, transmission electron microscopy, and immunohistochemistry enabled the discovery of five cell types with identified hormonal products in adult human pancreatic islets. Twentieth-century pancreatic studies led to crucial advances in scientific knowledge and were recognized, among other things, with seven Nobel Prizes. The first of these went to Ivan Pavlov in 1904 for his work on the physiology of digestion. The most recent was awarded to Günter Blobel in 1999 for discovering signaling mechanisms that govern the transport and localization of proteins within pancreatic acinar cells.